USING DIGITAL STORIES TO IMPROVE LISTENING COMPREHENSION WITH SPANISH YOUNG LEARNERS OF ENGLISH - Dolores Ramírez Verdugo; Isabel Alonso Belmonte (Language Learning and Technology)
This paper examines the effects that digital stories may have on the understanding of spoken English by a group of 6-year-old Spanish learners. To accomplish this aim, a quasi-experimental research study was launched in six state schools in Madrid. A pre-post test design was used to investigate whether internet-based technology could improve listening comprehension in English as a Foreign Language (henceforth, EFL). Findings indicate that the experimental group outperformed the control group in the final test administered. These results raise interesting issues related to the use of technology in the context of foreign language learning. Future research which includes other age groups and digital materials and which explores other linguistic areas could further substantiate the link between Information and Communication Technology (ICT) rich environment and improved language learning.